Method for recovering lithium compound
The method of recovering lithium compounds from used positive electrode reaction vessels by using cationic flocculating agents in a water-based filtration process addresses inefficiencies in existing methods, achieving high lithium recovery and purity.
Patent Information
- Application Number
- JP2023179938
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-19
AI Technical Summary
Conventional methods for recovering lithium compounds from used positive electrode reaction vessels are inefficient due to the use of corrosive acids and limited recovery of lithium ions, resulting in low yields and increased metal impurities.
A method involving the removal of positive electrode powder and precursor from the used reaction vessel, stirring the particles in water, filtering, and adding a cationic flocculating agent to the filtrate to recover lithium compounds, utilizing polyaluminum chloride or polymer flocculants as cationic flocculants.
This method allows for simple and efficient recovery of lithium compounds, achieving high lithium concentrations in the filtrate and effectively removing metal impurities, thereby improving the yield of lithium carbonate.
Smart Images

Figure 2025069972000001 
Figure 2025069972000002 
Figure 2025069972000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for recovering lithium compounds from a used positive electrode reaction vessel of a lithium secondary battery. [Background technology]
[0002] In lithium secondary batteries, the cathode material is produced in a reaction vessel (also called a reaction crucible). The raw material for the cathode material, lithium hydroxide (LiOH·H 2 O) is used in excess when mixed with the precursor and sintered to improve the high capacity performance of lithium secondary batteries, and as a result, after the cathode material is manufactured, the excess lithium component must be removed through a water washing process. In addition, the corrosion reaction of lithium hydroxide used in excess during the positive electrode material manufacturing process, which proceeds at high temperatures, corrodes the reaction vessels used in the production of positive electrode material, requiring replacement approximately every 30 days. Conventionally, used reaction vessels have been discarded, but because they contain high concentrations of lithium hydroxide, if the lithium compounds can be recovered and reused as positive electrode material, resources can be used more effectively.
[0003] Therefore, Patent Document 1 discloses a method for recovering nickel, cobalt, manganese and lithium compounds from a used reaction vessel.
[0004] [Patent Document 1] Korean Publication No. 102408888 Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional recovery methods require special equipment because they use highly corrosive sulfuric acid. In addition, when lithium compounds are extracted from used reaction vessels using acids such as hydrochloric acid, the amount of metals other than lithium recovered increases (especially aluminum), which reduces the yield of lithium compounds in the subsequent purification process. There are methods to selectively recover lithium using electrosorption, which uses a combination of a sorptive medium such as membrane capacitive deionization (MCDI) and an electric field; however, this method only processes lithium ions that are attracted to the electrode, which is problematic in that the amount of lithium recovered is low.
[0006] An object of the present invention is to provide a method for recovering lithium compounds simply and efficiently. [Means for solving the problem]
[0007] <1> The method for recovering lithium compounds of the present invention is a method in which particles obtained by pulverizing a used positive electrode reaction vessel from which the positive electrode material powder and the positive electrode material powder precursor have been removed are stirred in water, followed by filtration, adding a cationic flocculant to the obtained filtrate, and further filtering to recover lithium compounds. <2> The cationic flocculant is one or more selected from the group consisting of polyaluminum chloride and polymer flocculants. <1> A method for recovering lithium compounds. <3> The pulverized particles are particles that pass through a 0.5 mm mesh. <1> or <2> A method for recovering lithium compounds. <4> <1> ~ <3> A method for recovering lithium carbonate, comprising reacting the lithium compound obtained by any one of the recovery methods with sodium carbonate to obtain lithium carbonate. <5> <1> ~ <3> A method for recovering lithium carbonate, comprising reacting the lithium compound obtained by any one of the recovery methods with carbon dioxide to obtain lithium carbonate. Effect of the Invention
[0008] According to the present invention, a method for recovering lithium compounds simply and efficiently can be provided. Also, according to the present invention, a method for recovering lithium carbonate from lithium compounds can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The method for recovering lithium compounds of the present invention is a method in which particles obtained by pulverizing a used positive electrode reaction vessel from which the positive electrode material powder and the positive electrode material powder precursor have been removed are stirred in water, then filtered, a cationic flocculant is added to the obtained filtrate, and the filtrate is filtered again to recover lithium compounds.
[0010] The lithium compound recovery method of the present invention does not use a special device, but involves stirring the crushed particles of a used cathode reaction vessel from which the cathode material powder and the cathode material powder precursor have been removed in water, followed by filtration to obtain a filtrate. The obtained filtrate contains silicon compounds and aluminum compounds derived from the cathode reaction vessel in addition to lithium compounds. When a cationic flocculant is added to the obtained filtrate and stirred and mixed, the negatively charged fine particles in the filtrate and the positively charged cationic flocculant undergo a neutralization reaction to form flocculants. Then, filtration is performed to separate the flocculants, and an aqueous solution containing lithium compounds is obtained. Since silicon compounds and aluminum compounds are often negatively charged and form flocculants through a neutralization reaction with the cationic flocculant, they can be removed by filtration. The filtration can remove most of the metal compounds other than lithium, allowing efficient recovery of lithium compounds.
[0011] <Positive electrode reaction vessel> The positive electrode reaction vessel used in the present invention is not particularly limited as long as it is a positive electrode reaction vessel used in the manufacture of a positive electrode material for a lithium secondary battery. 2 O 3 -SiO 2 It is preferable to use a ceramic vessel based on MgO.
[0012] <Pretreatment of used positive electrode reaction vessel> Since a high concentration of cathode material powder precursors containing nickel, cobalt, manganese, lithium, etc. is deposited on the surface of the used cathode reaction vessel, these are collected and reused. As a result, lithium is the most abundant metal remaining in the used cathode reaction vessel after collection. Note that the cathode material powder and cathode material powder precursors may be removed from the used cathode reaction vessel to the extent possible, and a small amount may remain.
[0013] <Process for crushing used cathode reaction vessels> The process of crushing the used positive electrode reaction vessel is not particularly limited and can be appropriately selected according to the purpose. The process of crushing the used positive electrode reaction vessel can be, for example, a primary crushing process for roughly crushing the used positive electrode reaction vessel, and a secondary crushing process for crushing the used positive electrode reaction vessel to a certain particle size or less through a screen (a metal plate with holes) or the like. In the primary pulverization step, the positive electrode reaction vessel is roughly pulverized in a coarse pulverizer or a crusher to a size that can be fed into a fine pulverizer or an ultrafine pulverizer. In the secondary pulverization step, the roughly pulverized material is preferably pulverized in a fine pulverizer or an ultrafine pulverizer to a size of 0.5 mm or less. Examples of the crusher used in the primary crushing step include an impact crusher, a compression crusher, a cutting / shearing crusher, etc. Examples of the compression crusher include a jaw crusher, a gyratory crusher, a cone crusher, an impact crusher, etc. Examples of the crusher used in the primary crushing step include a single-shaft crusher, a double-shaft crusher, a hammer crusher, and a mobile crusher.
[0014] Examples of the fine pulverizer used in the secondary pulverization step include a roller mill, a jet mill, a high-speed rotary pulverizer, a vessel-driven mill, etc. Examples of the high-speed rotary pulverizer include a hammer mill and a pin mill, and examples of the vessel-driven mill include a rotary mill, a vibration mill, a planetary mill, etc. The secondary pulverization step can be carried out using an ultrafine pulverizer. Examples of the ultrafine pulverizer include a media agitation mill. Examples of the media agitation mill include an attritor and a bead mill.
[0015] A screen (metal plate with holes) can be used in the crusher used in the secondary crushing process. The objects to be crushed are discharged only if they are smaller than the size of the screen holes. There are no particular restrictions on the opening size of the screen and it can be selected appropriately depending on the purpose, but if a screen of 0.5 mm or less is selected, the particle size of the particles crushed from the positive electrode reaction vessel (hereinafter referred to as crushed particles) can be controlled to 0.5 mm or less. This allows the crushed particles to be selected as particles that pass through a 0.5 mm mesh. The extraction rate of lithium compounds in water is improved by crushing the particles to 0.5 mm or less.
[0016] <Process of stirring the crushed particles in water> Water is added in an amount of 3 times or more by mass to the crushed particles of 0.5 mm or less. The mixture is then heated and stirred at 30° C. or more for 10 minutes or more to extract the lithium compound into the water layer. The weight of the water used is preferably 3 times or more, more preferably 5 to 10 times, in consideration of the extraction efficiency of lithium. When the mass of water is 3 times or more the crushed particles, the extraction efficiency of the lithium compound is improved. Similarly, when the mass of water is 10 times or less, the separation efficiency in filtration is improved. When water is used, a hydrophilic solvent (e.g., alcohol, etc.) that is miscible with water can also be used.
[0017] The extraction temperature is preferably 30°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. The efficiency of extraction of lithium compounds into the aqueous layer increases in proportion to the increase in temperature. The extraction time is preferably 30 minutes or more, and more preferably 1 hour or more. The longer the extraction time, the higher the extraction rate of lithium compounds. However, the conditions will vary depending on the extraction equipment, etc.
[0018] <First filtration> The crushed particles are stirred in water, and then filtered to obtain a filtrate from which the crushed particles have been removed. The filtration method is not limited, but it is preferable to remove crushed products of 0.5 mm or less as much as possible. This suppresses the crushed particles and increases the recovery efficiency of the lithium compound. For this reason, for example, after filtering stepwise using filter paper with a coarse mesh to filter paper with a fine mesh, the crushed particles can be removed using a membrane filter. As the filter medium, various known filter media can be used. Filter media can be broadly classified according to material, structure, shape, and mesh size (also known as filtration accuracy).
[0019] Filter media materials can be broadly divided into inorganic compounds and organic compounds. Examples of inorganic compounds include metals such as titanium; alloys such as stainless steel and Hastelloy; metal oxides (ceramics) such as alumina, zirconia, and titanium oxide; silicon dioxide (glass) such as glass fiber, activated carbon, and diatomaceous earth. Examples of the organic compound include polyethylene, polypropylene, polyester, polyolefin, polyethylene terephthalate, polytetrafluoroethylene, polyurethane, polyacrylonitrile, polyvinylidene fluoride, perfluoroalkoxyalkane, cellulose phenol resin, nylon, nylon 66, rayon, acetate, polyphenylene sulfide, polyethersulfone, polysulfone, cotton, wool, and silk.
[0020] The structure of the filter media can be mesh, powder (particles), fiber, etc. The mesh is made by processing the filter material into fibers and weaving it in a regular pattern. The gaps between the fibers are used to capture coarse particles. Examples of weaving methods include plain weave, twill weave, tatami weave, and twill tatami weave. Powder is a form of filter media processed into fine particles. The fine particles are packed together and the gaps between the fine particles are used to capture larger particles. Fiber is a filter material that has been processed into fibers and entangled irregularly. It captures coarse particles by utilizing the gaps between the fibers. In addition to the above, other methods include a structure in which a void-free resin containing a solvent is made into a thin film and the solvent is evaporated to create tiny voids in the resin (phase inversion method), and a structure in which a void-free resin is made into a thin film and pulled to create tiny voids (stretching method).
[0021] The shape of the filter medium may be, for example, a disk filter, a membrane filter, a cartridge filter, etc. Examples of the cartridge filter include a depth filter, a pleated filter, a depth pleated filter, a thread wound filter, etc. A depth filter is a filter that uses a thick filter material placed on the outside of the cartridge core material to perform filtration by utilizing the thickness of the filter material. A pleated filter is a filter that has a thin filter material folded into pleats on the outside of the cartridge core, making use of the large surface area of the filter material to perform filtration. Depth pleated filters have a thick filter material folded into pleats around the outside of the cartridge core, and utilize the thickness and large surface area of the filter material to perform filtration. Depth filters have a thick filter medium with many voids that can capture coarse particles, making them suitable for filtering low-viscosity liquids with many coarse particles. Pleated filters have a thin filter medium with few voids that can capture coarse particles, making them suitable for filtering high-viscosity liquids with few coarse particles. Depth pleated filters combine the characteristics of both.
[0022] The mesh size (filtration accuracy) of the filter medium can be selected from any range of 1 nm to 1 mm depending on the size of the target object.
[0023] The mesh size (filtration accuracy) of a filter medium can be measured using the following method. If the mesh size of the filter medium is less than 50μm, ACFTD (natural particles with a particle size distribution of 50μm or less, as specified by ISO4402) is added as dust to the purified water, filtration is started at a flow rate of 10 liters / min, filtration is continued until the exchange differential pressure specified by the manufacturer is reached, and the filtrate is collected at the time the exchange differential pressure is reached. The number of particles in the solution before and after filtration is counted using a particle counter (BECKMAN COULTER HIAC9703+ (measurement range 0.5-600μm)), and the β value (filtration ratio) is calculated using the following formula (1). The particle size at which the β value is 1,000 or more (meaning that 99.9% or more of the particles have been removed) is taken as the mesh size of the filter medium (filtration accuracy).
[0024]
number
[0025] The filter medium is preferably structured to have a filtration gradient. A filtration gradient is a structure in which the mesh size of the filter medium decreases stepwise. By making the mesh size of the filter medium on the side that comes into contact with the solution before filtration the largest, and the mesh size of the filter medium on the side that the solution after filtration is discharged the smallest, coarse particles are removed stepwise from large particles to small particles, so that the coarse particles are efficiently removed and the life of the filter medium is extended, which is preferable.
[0026] The material of the filter medium used in the present invention is preferably, for example, polyethylene, polypropylene, polytetrafluoroethylene, or glass fiber. The filter medium preferably has a fiber structure, a structure obtained by a phase inversion method, or a structure obtained by a drawing method. The filter medium is preferably in the form of a depth filter or a depth pleats filter. The mesh size (filtration accuracy) of the filter medium is preferably from 1 to 500 μm, more preferably from 10 to 300 μm, and further preferably from 50 to 150 μm. By selecting the above filter media, coarse particles can be removed more efficiently.
[0027] Commercially available filter media include, for example, ROKI TECHNO's depth filter SLS series (material: polypropylene, structure: fiber, shape: depth, has filtration gradient), MPX series (material: polypropylene, structure: fiber, shape: pleats), CTY series (material: polytetrafluoroethylene, structure: structure that generates tiny voids by pulling, shape: membrane), SLP series (material: polypropylene, structure: fiber, shape: depth pleats), DIA-CS series (material: cotton, structure: fiber, shape: spool), SNN series (material: nylon, structure: fiber, shape: depth, has filtration gradient), MPS series (material: polyester, structure: fiber, shape: pleats); and the like.
[0028] The temperature during filtration is preferably from 5 to 80° C., more preferably from 15 to 60° C., and even more preferably from 20 to 45° C. The pressure during filtration is preferably from 0.01 to 2.00 MPa, more preferably from 0.02 to 1.00 MPa, and even more preferably from 0.03 to 0.5 MPa.
[0029] <Addition of cationic flocculant and second filtration> The obtained filtrate contains silicon compounds and aluminum compounds from the positive electrode reaction vessel in addition to lithium compounds. When a cationic flocculant is added to the obtained filtrate and stirred, the cationic flocculant neutralizes the negatively charged fine particles in the filtrate and the positive charges to produce flocculants. Then, filtration is performed to separate the flocculants, and an aqueous solution containing lithium compounds is obtained. Silicon compounds and aluminum compounds are often negatively charged and produce flocculants through a neutralization reaction with the cationic flocculant, so they can be removed by filtration. The filtration can remove most of the metal compounds other than lithium, so the lithium compounds can be efficiently recovered. The lithium concentration of the second filtrate after the second filtration is usually 50% or more by ICP analysis. If the lithium concentration is less than 50%, the efficiency of isolating lithium in the subsequent purification process decreases.
[0030] Examples of cationic flocculants include inorganic flocculants and polymer flocculants. Examples of inorganic flocculants include aluminum sulfate, polyaluminum chloride (PAC), ferric chloride, polyferric sulfate, ferrous sulfate, hydrated lime, seawater, etc. Among these, polyaluminum chloride is preferred in terms of flocculation efficiency. The polymer flocculant may, for example, be a cationic polymer flocculant. If a polymer flocculant is added to the flocculants to which an inorganic flocculant has been added, larger flocculants are generated, which makes it easier to separate in the subsequent filtration process. For example, a cationic polymer flocculant is essential, but an anionic flocculant or a nonionic flocculant can also be appropriately selected and used.
[0031] The amount of the cationic flocculant used is preferably 0.05 to 0.40 parts by mass, more preferably 0.10 to 0.30 parts by mass, per 100 parts by mass of the filtrate. When an appropriate amount is used, the flocculation efficiency of silicon compounds and aluminum compounds is improved, and filtration becomes easier.
[0032] The filtration is not limited as long as it can remove the aggregates. It is preferable to filter with a filter having a pore size of 5 μm or less. This can prevent the filtrate from being contaminated with cationic flocculants or metal compounds other than lithium. The filtration can be performed multiple times, for example, by using a filter with a smaller pore size and a filter with an even smaller pore size. The filter may be any of the filter media already described above. For example, the filter may be a membrane filter such as a cellulose mixed ester type membrane filter, a cellulose acetate type membrane filter, a PTFE type membrane filter, a hydrophilic PTFE type membrane filter, a polycarbonate type membrane filter, or a coated type filter.
[0033] The pore size of the filter is preferably 5 μm or less, more preferably 0.1 μm or less. It is preferable to perform a pretreatment before filtering with the filter. The pretreatment is performed to remove large aggregates using a filter medium with a large filtration size to prevent clogging of the filter. Pretreatment can be performed multiple times by preparing multiple filter mediums with filtration sizes of large, medium, and small. Examples of filter media used in pretreatment include ROKI TECHNO's depth filter SLS series (material: polypropylene, structure: fiber, shape: depth, has a filtration gradient), MPX series (material: polypropylene, structure: fiber, shape: pleats), CTY series (material: polytetrafluoroethylene, structure: structure that generates tiny voids by pulling, shape: membrane), SLP series (material: polypropylene, structure: fiber, shape: depth pleats), DIA-CS series (material: cotton, structure: fiber, shape: spool), SNN series (material: nylon, structure: fiber, shape: depth, has a filtration gradient), and MPS series (material: polyester, structure: fiber, shape: pleats).
[0034] <Step of isolating lithium carbonate from the obtained lithium extract solution> The method for recovering lithium carbonate of the present invention is a method for obtaining lithium carbonate by reacting the lithium compound obtained by the above-mentioned recovery method with sodium carbonate. The resulting lithium-containing extract is mixed with hydrochloric acid in an amount equal to or greater than the amount of lithium to produce lithium chloride. Next, an aqueous solution of sodium carbonate in an amount equal to or greater than the amount of hydrochloric acid is added to produce crystals. The crystals are then collected by filtration and the water is removed to produce lithium carbonate.
[0035] Another method for recovering lithium carbonate according to the present invention is a method for obtaining lithium carbonate by reacting the lithium compound obtained by the above-mentioned recovery method with carbon dioxide. Hydrochloric acid equivalent to or greater than the amount of lithium is added to the resulting lithium-containing extract to produce lithium chloride. Then, carbon dioxide is reacted to precipitate crystals. The crystals are collected by filtration, and lithium carbonate is obtained by removing water. The preferred method of introducing carbon dioxide is to bubble it into the extract, and the reaction temperature is preferably 25°C to 100°C, and more preferably 60°C to 100°C. If the temperature is below 25°C, the reaction proceeds slowly. Lithium carbonate can also be obtained by adding hydrochloric acid to the lithium extract to produce lithium chloride, which can then be reacted with sodium carbonate or carbon dioxide. EXAMPLES
[0036] The present invention will be specifically described below with reference to examples. However, the present invention is not particularly limited to the examples. In the examples, "parts" means "parts by mass" and "%" means "% by mass".
[0037] Example 1 A cathode reaction vessel (main component: Al) used for 30 days for the production of nickel, cobalt and manganese series cathode materials 2 O 3 -SiO 2 -MgO), and then the surface was washed with water to remove the positive electrode material powder and the positive electrode material powder precursor, to prepare a used positive electrode reaction vessel. The used positive electrode reaction vessel was subjected to primary crushing with a jaw crusher to obtain a coarsely crushed product. The obtained coarsely crushed product was subjected to secondary crushing with a Makino type crusher (model name: DD-2-3.7, manufactured by Makino Sangyo Co., Ltd.) at a rotation speed of 3500 rpm to obtain a pulverized product. The obtained pulverized product was subjected to a stainless steel screen with a mesh size of 0.5 mm to obtain pulverized particles with a particle diameter of 0.5 mm or less. In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 200 parts of the obtained pulverized particles and 1,000 parts of distilled water were charged and stirred for 1 hour at 90° C. The obtained slurry was filtered with a membrane filter (cellulose mixed ester type, pore size 3 μm, manufactured by ADVANTEC Corporation) to obtain 950 parts of a first filtrate. The first filtrate thus obtained was subjected to ICP (inductively coupled plasma) analysis, and as a result, it was found that 44.5% of the filtrate was lithium atoms. Next, 400 parts of the first filtrate was stirred while polyaluminum chloride (Al 2 O 3 3.0 parts of 1,2-dichloroethane (30%) was added and stirred for 1 hour. This solution was filtered through a membrane filter (cellulose mixed ester type, pore size 0.1 μm, manufactured by ADVANTEC) to remove the cationic flocculant aggregates and obtain a second filtrate containing a lithium compound. The main component of the lithium compound was lithium hydroxide.
[0038] <Lithium concentration evaluation> The obtained second filtrate was subjected to ICP analysis (instrument name: ICP-OES (inductively coupled plasma optical emission spectrometry, Agilent 720-ES)). As a result of the analysis, the ratio of lithium atoms in the non-volatile matter was 92.4%. The content of lithium atoms in the second filtrate was evaluated in terms of recovery efficiency according to the following criteria.
[0039] <Lithium recovery amount> The total amount of lithium contained in 1 g of the second filtrate obtained by treating crushed particles of used positive electrode reaction vessels (hereinafter referred to as particles) is 2500 ppm / 1 g of crucible or more, ◯ Good The total amount of lithium contained in 1 g of the second filtrate after treating the particles is 1000 ppm / 1 g of crucible or more. △ Practical use is possible. The total amount of lithium contained in 1 g of the second filtrate after treating the particles is less than 1000 ppm / 1 g of crucible × Not practical
[0040] <Lithium purity> In order to efficiently extract lithium compounds from the second filtrate, it is preferable that the lithium atom concentration is at least a certain level. From this viewpoint, the evaluation was made based on the following criteria. Lithium atom ratio is 90% or more. ◎Excellent Lithium atom ratio is between 70% and 90%. Good. Lithium atom ratio is between 60% and 70% △ Practical range Lithium atom ratio is less than 60% × Not practical
[0041] (Examples 2 to 7, Comparative Example 1) The same procedure as in Example 1 was carried out except that the recovery method in Example 1 was changed to the conditions shown in Table 1, and the lithium compounds were recovered by the methods in Examples 2 to 7 and Comparative Example 1, respectively.
[0042] [Table 1] JPEG2025069972000003.jpg112152
[0043] As can be seen from the results in Table 1, in Examples 1 to 7, the use of a cationic flocculant makes it possible to recover lithium compounds at high concentrations while suppressing contamination of the second filtrate with silicon compounds. Example 8 15.3 parts of 35% hydrochloric acid was added to 300 parts of the second filtrate obtained in Example 1, and then a solution in which 15.6 parts of sodium carbonate was dissolved in 68.0 parts of water was added. 360 parts of water was removed using a rotary evaporator, and the resulting slurry was filtered through a membrane filter (cellulose mixed ester type, pore size 0.1 μm, manufactured by ADVANTEC). The resulting filtrate was then dried at 200° C. for 10 minutes to obtain 1.2 parts of a white solid. The white solid was confirmed to be lithium carbonate by XRD analysis. The lithium concentration was 98.6% as a result of ICP analysis.
[0044] Example 9 15.3 parts of 35% hydrochloric acid was added to 300 parts of the second filtrate obtained in Example 1, and the mixture was stirred for 2 hours while blowing in carbon dioxide. 290 parts of water was removed using a rotary evaporator, and the resulting slurry was filtered through a membrane filter (cellulose mixed ester type, pore size 0.1 μm, manufactured by ADVANTEC). The resulting filter cake was then dried at 200° C. for 10 minutes to obtain 0.8 parts of a white solid. The white solid was confirmed to be lithium carbonate by XRD analysis (XRD (Rigaku SmartLab)). The lithium concentration was 96.4% as a result of ICP analysis.
[0045] As shown in the results of Examples 8 and 9, lithium carbonate can be recovered from lithium compounds.
Claims
1. A method for recovering lithium compounds, comprising: grinding a used positive electrode reaction vessel from which the positive electrode material powder and the positive electrode material powder precursor have been removed, stirring the resulting particles in water, filtering the resulting filtrate, adding a cationic flocculant to the filtrate, and filtering the filtrate further.
2. 2. The method for recovering a lithium compound according to claim 1, wherein the cationic flocculant is at least one selected from the group consisting of polyaluminum chloride and polymer flocculants.
3. 2. The method for recovering a lithium compound according to claim 1, wherein the pulverized particles are particles that pass through a mesh with an opening of 0.5 mm.
4. A method for recovering lithium carbonate, comprising reacting the lithium compound obtained by the method according to any one of claims 1 to 3 with sodium carbonate to obtain lithium carbonate.
5. A method for recovering lithium carbonate, comprising reacting the lithium compound obtained by the method according to any one of claims 1 to 3 with carbon dioxide to obtain lithium carbonate.
Citation Information
Patent Citations
Method for producing transition metal hydroxide
JP2011230957A
Lithium extraction method
JP2016191143A
Method for recovering valuable metals and material containing zeolite from waste cathode material reaction vessel
KR102408888B1